Proposta de eficientização energética do laboratório de Engenharia Elétrica UFPA/Camtuc para obtenção da certificação segundo o Procel - VALENTE, Fábio Nazareno (2018)
This work is proportionality purpose An Energy Efficiency of Electrical Engineering Laboratory of the Federal University of Pará, UFPA, Campus Tucuruí-PA, based tendon As OS Requirements Quality Technicians of Energy Efficiency Level Buildings Commercial, Service and Public ( RTQ-C). The RTQ-C boasts three study requirements for the label of certification:. Envelopment, Lighting System and Air Conditioning System Study Of these three requirements will result in the general classification of the building. Once que, this work will carry out a partial analysis, IE individual hair form Requirement: Air Conditioning System, SO, issuing a partial certification of the building. The Energy Efficiency of Electrical Engineering Laboratory - LEE, UFPA / CAMTUC, do qua collected the data to identify whether Meets as standards of the Brazilian Association of Technical Standards (ABNT), with the aim of reaching the National Conservation Label energy (ENCE), issued hair National Institute of Metrology, Standardization and industrial Quality (Inmetro). Therefore, if the (LEE), not serve as standards of ABNT, Sera Procedure OS identify vulnerable points and try enough pro them in relation Energy Efficiency for Medium evaluation using OS appropriate criteria que um provide partial result, qua will ratify the type of label That analysis Building match.